(untitled) (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2013)
Objective: To estimate the arch width in first permanent molar tooth in the normal occlusion of Bangladeshi population. Method: This cross sectional study was conducted among the students of Dhaka Dental College & Hospital, Mirpur- 14, Dhaka-1206. Total number of subjects were hundred, among them fifty were male and fifty were female .Mean age was 23.3 years. The study was conducted from October-2004 to September -2007. Results: The inter molar arch width in male upper jaws were 36.15mm, 43.45mm, 53.82mm respectively and in lower jaw these were 27.2mm, 36.01mm and 46.55mm. The transverse values in female upper jaw were 34.01mm, 41.26mm 51.43mm respectively and in lower jaw these were 26.12mm, 33.84mm and 44.31mm. Conclusion: The idea of a single arch width could not be substantiated in the study. But the result of the study might help clinicians to define normal arch width and their variations more precisely. However, there are scopes left for the researchers to work further over the issue. DOI: http://dx.doi.org/10.3329/bjodfo.v1i2.15983 Ban J Orthod & Dentofac Orthop, April 2011; Vol-1, No.2, 5-8